2016
DOI: 10.1103/physrevlett.116.178101
|View full text |Cite
|
Sign up to set email alerts
|

Untangling Knots Via Reaction-Diffusion Dynamics of Vortex Strings

Abstract: We introduce and illustrate a new approach to the unknotting problem via the dynamics of vortex strings in a nonlinear partial differential equation of reaction-diffusion type. To untangle a given knot, a Biot-Savart construction is used to initialize the knot as a vortex string in the FitzHugh-Nagumo equation. Remarkably, we find that the subsequent evolution preserves the topology of the knot and can untangle an unknot into a circle. Illustrative test case examples are presented, including the untangling of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
35
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 23 publications
3
35
1
Order By: Relevance
“…We strengthen these results, and for the unknot those of Ref. [13], by testing the bulk untangling dynamics of all of these knots with a wide variety of initial conditions -in the case of the unknot, a far greater variety than has been used previously. We find that in the bulk a generic unknot, trefoil or figure eight simplifies to a canonical form, but that the wave slapping mechanism at play for large N can cause rates of convergence to vary dramatically.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…We strengthen these results, and for the unknot those of Ref. [13], by testing the bulk untangling dynamics of all of these knots with a wide variety of initial conditions -in the case of the unknot, a far greater variety than has been used previously. We find that in the bulk a generic unknot, trefoil or figure eight simplifies to a canonical form, but that the wave slapping mechanism at play for large N can cause rates of convergence to vary dramatically.…”
Section: Introductionsupporting
confidence: 64%
“…So far, the striking knot simplification has been reported only for the unknot [13] -reducing three examples of tangled, but unknotted, curves to a geometric circle of fixed average radius -and, in two examples, the trefoil [13,14]. At higher crossing number the behaviour appears to be more complicated.…”
Section: Introductionmentioning
confidence: 95%
“…To date, the only evidence [8] over long time scales for this conjecture has been restricted to the simplest nontrivial knot, the trefoil knot, and some very recent results on the untangling of unknots [9]. Here we provide evidence for this conjecture by presenting solutions for all torus knots up to crossing number 11.…”
mentioning
confidence: 74%
“…These results reveal that the amplitude of the oscillation in the length decreases as p increases but increases as q increases. It has been shown that FitzHugh-Nagumo flow is able to untangle unknots with a complex initial conformation [9], but the physical mechanism that underpins this process remains elusive. Although the untangling dynamics is highly nontrivial, a phenomenological understanding, applicable in the regime of slight curvature and twist, can be obtained by combining positive filament tension [16,17] with a short-range repulsion between vortex strings.…”
mentioning
confidence: 99%
See 1 more Smart Citation